Construction of 3D Skeleton for Polymer Composites Achieving a High Thermal Conductivity - Yao, Yimin; Sun, Jiajia; Zeng, Xiaoliang; Sun, Rong; Xu, Jian‐Bin; Wong, Ching‐Ping (Small (Weinheim an der Bergstrasse, Germany), 2018)
Owing to the growing heat removal issue in modern electronic devices, electrically insulating polymer composites with high thermal conductivity have drawn much attention during the past decade. However, the conventional method to improve through‐plane thermal conductivity of these polymer composites usually yields an undesired value (below 3.0 Wm−1 K−1). Here, construction of a 3D phonon skeleton is reported composed of stacked boron nitride (BN) platelets reinforced with reduced graphene oxide (rGO) for epoxy composites by the combination of ice‐templated and infiltrating methods. At a low filler loading of 13.16 vol%, the resulting 3D BN‐rGO/epoxy composites exhibit an ultrahigh through‐plane thermal conductivity of 5.05 Wm−1 K−1 as the best thermal‐conduction performance reported so far for BN sheet‐based composites. Theoretical models qualitatively demonstrate that this enhancement results from the formation of phonon‐matching 3D BN‐rGO networks, leading to high rates of phonon transport. The strong potential application for thermal management has been demonstrated by the surface temperature variations of the composites with time during heating and cooling. An oriented phonon‐matching skeleton is developed based on two kinds of 2D materials for efficient thermal conduction in polymer composites via ice‐templated assembly technology. This development leads to significantly improved through‐plane thermal conductivity for polymer composites when compared with traditional strategies, suggesting strong potential in thermal management. The results would benefit the design of novel thermal‐management materials.